Sophie Halaby in Jerusalem : an artist's life - Schor, Laura S. (Syracuse University Press, 2019)
This manuscript is both a biography of an artist, Sophie Halaby, and a history of Jerusalem as seen through her eyes. Schor seeks to bring Halaby's story and that of Christian Arabs of Jerusalem to the English-reading public, as well as to look through this artist's eyes at the history of Jerusalem--a history often viewed through the lens of growing nationalism and punctuated by a series of violent events.